Minimizing water and nutrient losses from soilless cropping in southern Europe - Massa, Daniele; Magán, Juan José; Montesano, Francesco Fabiano; Tzortzakis, Nikos G. (My University, 2020)
In agriculture, soilless cropping represents the most suitable cultivation technique apt to achieve a theoretical 100 % efficiency of water and nutrient use. This is possible through a high control of input streams in the cultivation system. Soilless cultivation indeed allows high precision in nutrient and water management so that particular agronomic techniques, which are risky in other cultivation systems (e.g., nutrient depletion or the maintenance of low nutrient concentrations in the root zone), can be managed more safely under soilless conditions. Even in the so-called open (free-drain) cycles, water and nutrient losses can be minimized by the combination of sensing technologies and nutrient delivery strategies aiming at “zero emissions”. However, soilless cropping allows collection and reuse of the drainage in closed growing systems, thereby avoiding or minimizing water and nutrient losses into the environment. The main challenge when managing closed systems in southern Europe conditions is usually the progressive salinization of the recirculating solution because of saline irrigation waters often available in many in coastal areas of the Mediterranean. The use of alternative water sources like rainwater or desalinated water can prevent this problem, but their availability is limited. Advanced recirculation strategies have demonstrated a high potential for reusing the solution under saline conditions with optimal use and minimal discharge of nutrients. Hence, there is currently enough knowledge to support a larger application of closed soilless systems in Mediterranean conditions. On the other hand, proper choices in terms of cultivation facilities and structures and plant material can be relevant to achieve high water and nutrient use efficiency. The main relevant techniques (e.g., nutrient solution management strategies, and right choice of planting material) and technologies (e.g., sensing technologies and greenhouse structures) to minimize water and nutrient losses from soilless-grown vegetable crops in southern Europe are reviewed in this paper.
Keywords: Circular horticulture; Greenhouse; Hydroponics; Nutrient and water use efficiency; Precision agriculture; Salinity; Vegetables